LIVER DISEASE IN CHILDREN WITH CYSTIC FIBROSIS - Laura Mihaela Trandafir; Iulia Straticiuc Ciongradi; Ginel Baciu; Dana Teodora Anton Păduraru (Amaltea Medical Publishing House, 2014)
Liver disease is an early complication in children with cystic fi brosis (CF).The clinical manifestations in hepatobiliary disease of CF include neonatal cholestasis, liver steatosis, liver fi brosis, biliary lithiasis, focal biliary cirrhosis and multilobular cirrhosis, with or without portal hypertension. Changes in the tests evaluating the liver function are inconsistent and are not correlated with the severity of the liver lesions. The diagnosis of liver disease in CF requires the presence of at least two of the following four diagnosis criteria:clinical manifestations, pathologic liver function tests, ultrasound and histologic changes.The annual follow-up to evaluate the liver function is s recommended for diagnosis of asymptomatic liver disease and early initiation of treatment with ursodeoxycholic acid.The improvement of the liver function infl uences life quality and increases the survival rate in patients with CF.